Boninites in the ~3.3 Ga Holenarsipur Greenstone Belt, Western Dharwar Craton, India - Tarun C. Khanna; V. V. Sesha Sai; S. H. Jaffri; A. Keshav Krishna; M. M. Korakoppa (Geosciences, 2018)
In this contribution, we present detailed field, petrography, mineral chemistry, and geochemistry of newly identified high-Si high-Mg metavolcanic rocks from the southern part of the ~3.3 Ga Holenarsipur greenstone belt in the western Dharwar craton, India. The rocks occur as conformable bands that were interleaved with the mafic-ultramafic units. The entire volcanic package exhibits uniform foliation pattern, and metamorphosed under greenschist to low grade amphibolite facies conditions. The rocks are extremely fine grained and exhibit relict primary igneous textures. They are composed of orthopyroxene and clinopyroxene phenocrysts with serpentine, talc, and amphibole (altered clinopyroxene). Cr-spinel, rutile, ilmenite, and apatite occur as disseminated minute grains in the groundmass. The mineralogical composition and the geochemical signatures comprising of high SiO2 (~53 wt. %), Mg# (~83), low TiO2 (~0.18 wt. %), and higher than chondritic Al2O3/TiO2 ratio (~26), reversely fractionated heavy rare earth elements (REE) (GdN/YbN ~ 0.8), resulting in concave-up patterns, and positive Zr anomaly, typically resembled with the Phanerozoic boninites. Depletion in the high field strength elements Nb, and Ti relative to Th and the REE in a primitive mantle normalized trace element variation diagram, cannot account for contamination by pre-existing Mesoarchean continental crust present in the study area. The trace element attributes instead suggest an intraoceanic subduction-related tectonic setting for the genesis of these rocks. Accordingly, the Holenarsipur high-Si high-Mg metavolcanic rocks have been identified as boninites. It importantly indicates that the geodynamic process involved in the generation of Archean boninites, was perhaps not significantly different from the widely recognized two-stage melt generation process that produced the Phanerozoic boninites, and hence provides compelling evidence for the onset of Phanerozoic type plate tectonic processes by at least ~3.3 Ga, in the Earth’s evolutionary history.